Exploring bio-remediation strategies by a novel bacteria Micrococcus sp. strain HX in Cr(VI)-contaminated groundwater from long-term industrial polluted - Yu Xia; Yujuan Wen; Yuesuo Yang; Xiaoming Song; Yunlong Wang; Zhipeng Zhang (Ecotoxicology and Environmental Safety)
Hexavalent chromium (Cr(VI)) has emerged as a contaminant of heavy metal, owing to its wide use in industry. This study focuses on elucidating the interaction between microbial communities and environmental parameters in Cr(VI)-contaminated groundwater near a factory in Henan Province, and evaluating the bio-remediation potential of microorganisms toward Cr(VI) reduction. The highest concentration of Cr(VI) in the groundwater is 208.08 mg/L. The dominant microbes were Proteobacteria and Bacteroidota, closely positively related to Cr(VI) and SO42-. Many of these genus have been proven to be chromium tolerant or have the ability to reduce Cr(VI). Two strains, Micrococcus sp. HX and Bacillus sp. HX-2, were isolated from contaminated groundwater, and Micrococcus sp. HX was used for the first time to reduce Cr(VI) in groundwater. The reduced ability of HX reached 90.18 % at a Cr(VI) concentration of 100 mg/L, while HX-2 achieved a reduction capacity of 63.8 %. Micrococcus sp. HX shows the best reduction efficiency in alkaline environments (ph=8), which is close to the tannery industry wastewater. The reduction efficiency by Micrococcus sp. HX reached 67.26 % in groundwater samples (Cr(VI)= 26.08 mg/L). Transcriptome analyses revealed oxidoreductase activity, ATP binding and the NAD(P) binding region protein-related gene expression were up-regulated. Binding reduction experiments indicated that most of the Cr(III) was detected extracellular, which suggests that the reduction of Cr(VI) by HX was mainly extracellular enzyme-catalyzed.